Pengaruh Variasi Ketebalan Square Tube Din 10305-5 Terhadap Defleksi Rangka Plastic Shredder - Karmiati, Besse Titing; Ikaningsih, Manty Aldilani; Rosihan, War’an; Saefudin, Deny Bayu; Pessireron, Agneta Grace (Pusat Penelitian dan Pengabdian kepada Masyarakat, Politeknik Negeri Balikpapan, 2024)
shredder used square mild steel tubes 30 mm x 30 mm with 3 mm thickness close to DIN 10305-5 standard specification for square tubes in Indonesia. This 3 mm thickness square tube was rare in Indonesia because most hardware shops only sell variants with a maximum thickness of 2 mm. The effect of tube thickness variation on frame deflection is the primary concern in this research. The frame analysis method is used to calculate maximum deflection on the frame. The square tube thickness value varied from 3 mm, 2 mm, and 1mm. As the results obtained, it was found that the maximum deflection occurred in the tube which has a thickness of 1 mm by 0.065 mm. While on a tube that has a thickness of 3 mm, the maximum deflection is 0.031 mm. And in order to maintain the value of maximum deflection less than or equal to 0.031 mm, minor modifications were applied to the frame design. The new frame design using square tubes thickness of 1 mm has a maximum deflection value of 0.029 mm, which is slightly better than the original design